Portal nasza-klasa.pl jako przykład strategii "błękitnego oceanu" - Wilk, Joanna (Nasza-Klasa.pl as an Example of the "Blue Ocean" Strategy, 2008)
The article describes the main idea and elements of the Blue Ocean Strategy and its significance in gaining the competitive advantage. It also shows the nasza-klasa.pl as the example of application of basic rules of the strategy into the business practice. Moreover, the paper presents the main factors of success and the perspectives of future development, as far as the possibilities of maintaining the competitive advantage that has been gained because of successful setting the boundaries of the market.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 404-414